2015
DOI: 10.1097/qad.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Association of HIV, hepatitis C virus and liver fibrosis severity with interleukin-6 and C-reactive protein levels

Abstract: Background Hepatitis C infection (HCV) is associated with chronic inflammation; yet studies show greater IL-6 but lower CRP levels. We determined whether liver fibrosis severity and HCV replication affect the ability of IL-6 to stimulate production of CRP from the liver. Methods We used multivariable generalized linear regression to examine the association of HIV, HCV and transient elastography-measured liver stiffness (LS) with IL-6 and CRP in participants (164 HIV-monoinfected; 10 HCV-monoinfected; 73 HIV/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 31 publications
9
37
0
Order By: Relevance
“…However, CRP, which was almost 50% higher in frail HIV+ men than in non-frail HIV+ men, was essentially identical in frail and nonfrail HIV− men. This discrepancy may be due at least in part to our deliberate inclusion of all HCV-infected HIV− men in the parent biomarker study; this infection can lower CRP levels 33 and was much more common in the HIV− frail men (42%) than in the HIV− nonfrail men (13%). Taken together, the present data suggest that inflammation is associated with frailty in HIV+ men as it is in elderly HIV− populations, but that the mechanisms of this association may differ between HIV− and HIV+ people in the age range studied here.…”
Section: Discussionmentioning
confidence: 98%
“…However, CRP, which was almost 50% higher in frail HIV+ men than in non-frail HIV+ men, was essentially identical in frail and nonfrail HIV− men. This discrepancy may be due at least in part to our deliberate inclusion of all HCV-infected HIV− men in the parent biomarker study; this infection can lower CRP levels 33 and was much more common in the HIV− frail men (42%) than in the HIV− nonfrail men (13%). Taken together, the present data suggest that inflammation is associated with frailty in HIV+ men as it is in elderly HIV− populations, but that the mechanisms of this association may differ between HIV− and HIV+ people in the age range studied here.…”
Section: Discussionmentioning
confidence: 98%
“…It is also possible that HCV itself is protective against HS, although the cross‐sectional nature of this study limits our ability to demonstrate this. C‐reactive protein levels are substantially reduced in the setting of chronic HCV, due in part to an attenuated response to interleukin (IL)‐6 in the presence of HCV . Both hepatic and serum levels of IL‐6 are elevated in patients with nonalcoholic fatty liver disease and nonalcoholic steatohepatitis, suggesting a role of IL‐6 in the pathogenesis of HS.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies have evaluated the effect of both HIV mono‐infection and HIV/HCV co‐infection on inflammatory biomarkers. (Table and Table S4) The majority of studies have found that HCV co‐infection further increases the serum levels of IL‐6, IL‐10, and sTNFRI but decreases levels of CRP or hsCRP irrespective of liver function . Shah et al found that CRP levels fell with increasing IL‐6 levels suggesting attenuation of the CRP‐related IL‐6 response .…”
Section: Special Populationsmentioning
confidence: 99%
“…(Table 3 and Table S3) Among CHC patients, elevated levels of BNP, NT-proBNP, 50,51,67,99,[125][126][127][128][129] TnT, and TnI 103,128 have been observed compared to healthy controls. ( Table 4 and Table S4) The majority of studies have found that HCV co-infection further increases the serum levels of IL-6, 133-138 IL-10, 139 and sTNFRI 138 but decreases levels of CRP or hsCRP 133,134,136,[140][141][142] irrespective of liver function. 133 Shah et al found that CRP levels fell with increasing IL-6 levels suggesting attenuation of the CRP-related IL-6 response.…”
Section: Biomarkers Of Cardiac Dysfunctionmentioning
confidence: 99%